Correlated X-ray spectral and timing behavior of the black hole candidate XTE J1550-564: A new interpretation of black hole states - Homan, Jeroen (2001)
We present an analysis of data of the black hole candidate and X-ray transient XTE J1550-564, taken with the Rossi X-Ray Timing Explorer between 1998 November 22 and 1999 May 20. During this period the source went through several different states, which could be divided into soft and hard states based on the relative strength of the high-energy spectral component. These states showed up as distinct branches in the color-color and hardness-intensity diagrams, connecting to form a structure with a comblike topology, the branch corresponding to the soft state forming the spine and the branches corresponding to the various hard states forming the teeth of the comb. The power spectral properties of the source were strongly correlated with its position on the branches. The broadband noise became stronger and changed from power law-like to band-limited, as the spectrum became harder. Three types of quasi-periodic oscillations (QPOs) were found: 1-18 Hz and 102-284 Hz QPOs on the hard branches, and 16-18 Hz QPOs on and near the soft branch. The 1-18 Hz QPOs on the hard branches could be divided into three subtypes. The frequencies of the high- and low-frequency QPOs on the hard branches were correlated with each other and were anticorrelated with spectral hardness. The changes in QPO frequency suggest that the inner disk radius only increases by a factor of 3-4 as the source changes from a soft to a hard state. Our results on XTE J1550-564 strongly favor a two-dimensional description of black hole behavior, where the regions near the spine of the comb in the color-color diagram can be identified with the high state, and the teeth with transitions from the high state, via the intermediate state (which includes the very high state) to the low state, and back. The two physical parameters under-lying this two-dimensional behavior vary to a large extent independently and could for example be the accretion rate through the disk and the size of the Comptonizing region causing the hard tail. The difference between the various teeth is then associated with the mass accretion rate through the disk, suggesting that high state ↔ low state transitions can occur at any disk mass accretion rate and that these transitions are primarily caused by another, independent parameter. We discuss how this picture could tie in with the canonical, one-dimensional behavior of black hole candidates that has usually been observed.